2019
DOI: 10.1063/1.5089294
|View full text |Cite
|
Sign up to set email alerts
|

Is Tollmien-Schlichting wave necessary for transition of zero pressure gradient boundary layer flow?

Abstract: Comprehensive understanding of the routes of instability and transition for many flows is not complete yet. For a zero pressure gradient (ZPG) boundary layer, linear spatial theory predicted Tollmien-Schlichting (TS) waves, which have been experimentally verified by vortically exciting the flow by a monochromatic source. This is the well-known frequency response of dynamical system theory. Natural transition in real flows occurs due to polychromatic excitation, and to simulate such transition, the ZPG boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The initial STWF transforms into a turbulent spot creating additional STWFs, which merge downstream to create the turbulent flow. The free-stream excitation case considered here is distinctly different from the wall-excitation case [35], as the local solution and the STWF continually interact for the former, while for the latter, these two components do not interact after the onset of STWF. As a consequence, the linear and nonlinear solutions are completely different for the free-stream excitation case.…”
Section: The Local Solution Is Indicated By (I) In Figs 2(c) and 2(d)mentioning
confidence: 82%
See 2 more Smart Citations
“…The initial STWF transforms into a turbulent spot creating additional STWFs, which merge downstream to create the turbulent flow. The free-stream excitation case considered here is distinctly different from the wall-excitation case [35], as the local solution and the STWF continually interact for the former, while for the latter, these two components do not interact after the onset of STWF. As a consequence, the linear and nonlinear solutions are completely different for the free-stream excitation case.…”
Section: The Local Solution Is Indicated By (I) In Figs 2(c) and 2(d)mentioning
confidence: 82%
“…[11,19,23,24]. Recently, it has been shown that the STWF is the definitive causal mechanism for the onset of transition to turbulence, irrespective of the nature of the imposed wall excitation [35]. For the same equilibrium flow in Refs.…”
Section: The Local Solution Is Indicated By (I) In Figs 2(c) and 2(d)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bhaumik et al (2017) and Sharma et al (2018) found that the modulation characteristics and consequently the features of the wavepacket change when one shifts from an impulsive monochromatic onset of excitation to a gradual monochromatic excitation. In the case of switching the exciter on and off (finite onset and termination of the exciter), it would result in the evolution of two subsequently phase-shifted and time-delayed spatio-temporal wavepackets as noted in Bhaumik (2013) and Sundaram et al (2019) for 2D disturbances -one wavepacket when the exciter is switched on, and another when the exciter is switched off, while the spatial Tollmien-Schlichting (TS) wavepacket/wavetrain recedes back.…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness has a rather complex influence on airfoil aerodynamics, since it can also effect the transition behavior. For a smooth surface, the boundary layer transition usually occurs with involvement of the Tollmein-Schlichting waves as the primary instabilities [4]. It is known that surface roughness alters the transition behavior due to the changes in the underlying mechanism and can also trigger an earlier transition, the modes of which being strongly dependent on the type of roughness.…”
Section: Introductionmentioning
confidence: 99%